Traditional medicine in a modern light: a scoping review on the osteoprotective potential of Eucommia ulmoides - Wang, Yuanzhong; Chen, Guiju; Wang, Qin; Liu, Bilin; He, Qi; Huang, Xia; Chin, Kok-Yong (Frontiers in Pharmacology, 2026)
Background/ObjectivesEucommia ulmoides (Du-Zhong), a traditional Chinese medicinal plant, has long been valued for its ability to strengthen bones and muscles. Recent research highlights its potential in supporting bone health and managing osteoporosis. This scoping review summarises existing evidence on the role of Eucommia ulmoides in osteoporosis prevention and treatment.MethodsA comprehensive literature search was conducted from inception to November 2025 across six databases: PubMed, Scopus, Web of Science, CNKI, Wanfang and CQVIP. Studies investigating the effects of Eucommia ulmoides extracts or its bioactive compounds on bone-related outcomes in cellular, animal, or human models of osteoporosis were included.ResultsNinety studies met the inclusion criteria. The evidence demonstrates that Eucommia ulmoides and its bioactive compounds, most notably aucubin, geniposide, rutin, and pinoresinol diglucoside, consistently promote osteoblastogenesis and inhibit osteoclastogenesis. These effects are mediated through the modulation of key signalling pathways, including BMP/SMAD, Wnt/β-catenin, OPG/RANKL, and MAPK/NF-κB. In animal models, the treatment improved bone mineral density (BMD), enhanced trabecular microarchitecture (increased bone volume fraction, trabecular number and thickness), and increased bone biomechanical strength. Clinical studies, while preliminary, reported that Eucommia ulmoides-based formulations (e.g., Quanduzhong capsules, Eucommia granules) were associated with improved BMD, reduced bone resorption markers, and alleviated clinical symptoms in osteoporotic patients.ConclusionThis scoping review consolidates a substantial body of evidence supporting the osteoprotective potential of Eucommia ulmoides. Its multi-targeted mechanism of action, targeting both bone formation and resorption, positions it as a promising candidate for the management of osteoporosis. The findings underscore the necessity for future research to prioritise standardised extract preparation, detailed pharmacokinetic studies, and rigorous, large-scale clinical trials to definitively establish its efficacy and safety in humans.